The characterization and identification of strain ACL-F-001A, an isolate cultured from aerobic granules acclimated for tertiary-butyl alcohol bioremediation - Wong, Kok How. (2010)
This project aims to identify and characterize the strain ACL-F-001A based on polyphasic approach. In polyphasic classification of bacteria below the genus level, extensive use of classification methods, which includes morphological descriptions, biochemical and physiological properties, chemotaxonomic data, DNA base composition, DNA: DNA hybridization data and phylogenetic analysis of rDNA genes, are required (T. Brinkhoff et al., 1998). However, in this project, all, except chemotaxonomic and DNA: DNA hybridization analysis, were carried out in this polyphasic approach of strain ACL-F-001A. This strain was isolated from the aerobic granules used for the bioremediation of tertiary-butyl alcohol in synthetic wastewater without carbon substrate source, which made the target strain to be of research interest. The strain ACL-F-001A was eventually found to belong to Sphingomonas sp. This finding was substantiated by the genotypic and phenotypic characterization of this target strain. In the genotypic characterization, phylogenetic analysis of the 16S rRNA was done. The phylogenetic tree constructed, together with the tabulation of DNA G+C content and the nucleotide signature, showed that strain ACL-F-001A was proposed to be a novel species of the genus Sphingomonas. This finding was supported by high bootstrap value, obtained from bootstrap analysis of the phylogenetic tree, and high similarity in nucleotide sequences, obtained from distance matrix between the target strain and representative species of Sphingomonas sp, e.g. Sphingomonas asaccharolytica and Sphingomonas pruni (97% and 96.7% respectively). A comparative study was done between strain ACL-F-001A and known species of genus Sphingomonas sp. This study included biochemical tests to determine the morphological and physiological characteristics of strain ACL-F-001A. Based on substrates utilization patterns and enzyme activities, it was observed that strain ACL-F-001A did not had the same physiological characteristics as any known representative species of Sphingomonas (cluster I). It was believed that this target strain could be a new strain of Sphingomonas sp. that was yet to be identified thus far.